ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN WHOLESALE AND RETAIL TRADE DI BURSA EFEK INDONESIA (Pengujian Empiris Menggunakan Client Cycle Time dan Firm Cycle time) - Ismail Mubaraq; Emrinaldi Nur Dp; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is to empirically examine the factors that affect audit delay in the Wholesale and Retail Trade company in Indonesia Stock Exchange. The dependent variable in this research is the breakdown of audit delay into Client Firm Cycle Time and Cycle Time. Independent variables are extraordinary items, corporate income, debt proportion, client size. This research uses secondary data. Namely the annual financial statements obtained from the office of Capital Market Information Center (PIPM) Pekanbaru. The analysis used is multiple linear regression using the enter method. The sample used in the research were taken using puposive sampling technique. The results showed that the Client Cycle Time is affected by corporate income variable, while the other independent variables are extraordinary, debt proportion and client size had no significant effect. For Firm Cycle Time study results showed that all independent variables are extraordinary items, corporate income, debt proportion and client size have a significant effect. From the test results are known Coefficient of Determination R2 Adjusted R Square value on Client Cycle Time by 0.259 which states that the contribution of the effect of independent variables on the dependent variable Client Cycle Time is of 25.9%. While the remaining 74.1% is influenced by other variables. And Cycle Time Firm known for the value of Adjusted R Square of 0.235 means that the effect is that the contribution of the independent variable on the dependent variable for Firm Cycle